Surface modification of mild steel using tungsten inert gas torch surface cladding - Dyuti, S.; Mridha, Shahjahan; Shaha, S. K. (Science Publications, 2010)
There is an increasing demand for claddings which possess an optimized combination of different functional properties such as high hardness, high resistance to wear and oxidation. In this respect, hard TiAlN cladding has gained much attention. These claddings can be suitable replacements for the conventional ceramic coatings applied in many components of chemical plants and automotive industries to protect against high temperature oxidation and wear. Approach: In this study the possibility of the formation of intermetallic and nitride claddings on plain carbon steel surfaces by in situ melting of preplaced titanium and aluminum powder mixture under Tungsten Inert Gas (TIG) torch had been investigated. Results: Addition of 1.3 and 1.8 mg mm-2 Ti and Al powder and melting at energy inputs between 540-675 J mm-1 in nitrogen environment successfully created more than 1 mm thick clad layer consisting of a mixture of titanium-aluminum nitrides and aluminides. All resolidified melt layers produced dendrite microstructures; the dendrite concentration is more near the surface area compared to the deeper melt depth. A maximum surface hardness of around 900 Hv was developed in most of the tracks and this hardness corresponds to high concentration of dendrites within the modified layer. Oxidation at 600°C for 72 h, of the clad steel gave weight gains of 0.13 mg mm-2, compared to 0.37 mg mm-2 for the substrate. Conclusion: The results showed that clad steel gave better mechanical and oxidation properties compared to plain carbon steel substrate.